Ūrmiḷā : Vālmīki Rāmāyaṇa ādhārita kādambari - Naḷini Mūrti (Maisūru : Gītā Buk Haus, 1988)
Based on Ūrmiḷā, character from the Rāmāyaṇa, extended narrative poem on Rāma (Hindu deity), by Vālmīki.
Novel.
In Kannada.
Keywords: Ūrmilā (Hindu mythology) -- Fiction; Rāma (Hindu deity) -- Fiction; Rāma -- (Hindu deity); Ūrmilā (Hindu mythology); Fiction